JAK2/STAT3 Pathway Was Associated with the Protective Effects of IL-22 On Aortic Dissection with Acute Lung Injury. (30th July 2017) - Ren, Wei; Wang, Zhiwei; Wu, Zhiyong; Hu, Zhipeng; Dai, Feifeng; Chang, Jinxing; Li, Bowen; Liu, Huagang; Ruan, Yongle
Abstract : Patients with aortic dissection (AD) may present acute lung injury (ALI) that may affect the prognosis. In this study, we aim to investigate the roles and mechanism of IL-22 in the pathogenesis of AD complicated with ALI. Six hundred and twenty-one AD patients were included, and the incidence of ALI and pulmonary CT findings were analyzed. Mouse ALI model was established through AngII, and then IL-22 injection and AG490 were given. The pathological changes, infiltration of inflammatory cells, and expression of STAT3 were determined. For the in vitro experiment, cultivated pulmonary microvascular endothelial cells (PMVECs) were treated by angiotensin II (AngII), followed by treating with IL-22 and/or AG490. The expression and migration of STAT3 was determined. Flow cytometry was carried out to evaluate the apoptosis. IL-22 contributed to the expression of STAT3 in lung tissues and attenuation of ALI. IL-22 obviously inhibited the apoptosis of PMVECs mediated by AngII and downregulated the expression and intranuclear transmission of STAT3. Such phenomenon was completely inhibited upon administration of AG490, an inhibitor of JAK2. Our data showed IL-22 contributed to the inhibition of PMVEC apoptosis mediated by AngII through activating the JAK2/STAT3 signaling pathway, which may attenuate the ALI induced by AngII.